Políticas de formação continuada do professor formador em um Centro de Formação e Atualização dos Profissionais da Educação Básica - Silva, Rosivete Oliveira da (2012)
This work is not in the context of reflections on the continuing education of teachers, as an object of study outlining the policy of continuing education teacher trainer at the Center for Professional Training and Upgrading of Basic Education - CEFAPRO Cuiabá-MT, from 2008 to 2009. The research is guided by the following question: who shape and how to configure the training of trainers of teachers CEFAPRO? This question aimed to understand who shape and how to configure policies for ongoing training of trainers of teachers CEFAPRO, the perspective of improving my own work, contribute to the formation process in CEFAPROs and policies of continuing education in the state. In the theoretical-methodological options, take to thread the elements of the design cycle policy of Ball (1992, 2001, 2006, 2009). The author describes a continuous cycle of policy and highlights three main contexts: the context of influence, text and practice. In this study we intend to go through the cycle of policy continued teacher trainers. The research methodology has a qualitative perspective, with historical and sociological approach. Data collection occurs via literature research, study records and interviews with those involved in continuing education in the period and confined space. In research it is considered that continuing education is a process of theoreticalpractical course that builds on the professional life of teachers. To define the understanding of training and continuing education of teachers resort to Contreras (2002), Gatti (2005, 2008), Garcia (2006), Giroux (1997), Gramsci (1982), Freire (1987, 1994); Nóvoa (1992, 1995, 1999, 2000, 2009) and Schön (1992). The result of the study analyzed the documents and interviews indicate that no single policy in the state of Mato Grosso to the continuing education of teacher educators, but many continued education policies, realized from the projects and programs; of general training offered by SEDUC and decisions taken by teachers in the CEFAPRO. Of note is the project "Teacher Trainer's Room," a locus in training that seeks to create opportunities teacher trainer training to assist in carrying out their work to meet all levels and types of education, according to area / Discipline. Thus, I conclude that the trainers of teachers CEFAPRO Cuiabá are under the influence of contradictory processes of continuous formation. Projects and programs reinforce state intervention, which legitimizes the technical training and teaching work of teacher educators, removing them the professional autonomy, and the "Project Room Teacher Trainer", somehow develops in teacher trainer autonomy of their pedagogical training. I point to the urgent need for action SEDUC / MT partnering with universities in order to allow training to trainers of teachers CEFAPRO in a non-fragmented, but actually continued.